Relationship between body shape and performance in Japanese elite collegiate male swimmers: use of a 3-D homologous body model - Soma, M.; Kashiwagi, Y.; Funato, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2022)
The purpose of this study was to examine the relationship between morphological characteristics and performance in Japanese elite swimmers and non-athletes. The participants included Japanese elite swimmers (age: 20.8 ± 1.7 yr, height: 173.4 ± 5.7 cm, weight: 70.1 ± 6.0 kg, FINA points: 805 ± 72) and non-athletes (age: 19.8 ± 2.4 yr, height: 171.1 ± 5.7 cm, weight: 62.1 ± 8.9 kg). A 3-D whole-body line scanner (BLS; Hamamatsu Photonics) in contact with the skin was used to scan the standing whole body of each subject. Body fat was measured using an air displacement plethysmograph, which uses BODPOD (Body Composition System Mab-1000) to determine body composition (body fat and lean body mass). A homologous body model (HBM) was constructed by fitting the whole-body laser scan polygon data to a generic template model based on anatomical landmarks. The HBM consisted of 20,000 vertex of the same topology, and each data point was calculated based on the anatomical landmarks. SDs were used for principal component analysis. For examining the relationship with competition performance, the International Swimming Federation (FINA) points system was adopted. FINA points scores allow comparisons of results among different events. The points (P) are calculated from the swim time (T) and the base time (B) in seconds using the following formula: P = 1000 * (B / T) 3 The results obtained were as follows: (1) The data on 3-D human body shape obtained using the BLS and BODPOD revealed that in comparison nonathletes, the swimmers had a significantly higher body weight, BMI, lean body mass and chest (p<0.001), and a significantly smaller abdominal circumference/chest circumference ratio. (2) When normalized to body height, swimmers had larger chest, abdominal and latissimus dorsi muscles. (3) The FINA points score was associated with body shape. The HBM of the 3-D body shape made it possible individual differences and characteristics of body shape. These results suggest that a specific somatotype is required to reach an elite level in sport, and that there is a need to integrate somatotype data between scientific instruments for selecting talent in artistic swimmers. Principal component analysis of the HBM made it possible to establish a method for quantification of 3-D body shape. The present findings suggest that use of a HBM reveals details of body shape that cannot be achieved from morphological measurement, thus opening a new perspective for sports research.